2020
DOI: 10.1101/2020.07.25.221135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 and SARS-CoV spike-mediated cell-cell fusion differ in the requirements for receptor expression and proteolytic activation

Abstract: The SARS-Coronavirus-2 (SARS-CoV-2) infects cells through interaction of its spike protein (SARS-CoV-2-S) with the ACE2 receptor and activation by proteases, in particular TMPRSS2. Viruses can also spread through fusion of infected with uninfected cells. We therefore analyzed cell-cell fusion activity of SARS-CoV-2-S with regard to the requirements for ACE2 expression, proteolytic activation, and sensitivity to inhibitors and compared it to SARS-CoV-S. We compared S-protein-driven fusion with target cells reco… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 61 publications
12
55
1
Order By: Relevance
“…However in a recent study, unlike Camostat, another known TMPRSS2 inhibitor; AMB and BHH did not reverse TMPRSS2-mediated enhancement of SARS-CoV-2 infection in 293Tcells 48 .…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…However in a recent study, unlike Camostat, another known TMPRSS2 inhibitor; AMB and BHH did not reverse TMPRSS2-mediated enhancement of SARS-CoV-2 infection in 293Tcells 48 .…”
Section: Discussionmentioning
confidence: 76%
“…Our biochemical findings are most complementary to the report by Hornich, B.F. et. al., that observed inhibition of SARS-CoV-2-S-mediated fusion in the presence of 50 µM AMB 48 ; but observed a dose dependent enhancement of SARS-CoV-2-S-mediated fusion by BHH at the concentrations tested 48 . Furthermore, a computational transcriptomics study by Napolitano, F. et al 53 , found that AMB induced an opposite transcriptional profile compared to that induced by SARS-CoV-2 infection in vitro, suggesting that it may be playing a role in counteracting viral infection 53 .…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations